Assessment of the functional state of boxers by complex results of rhythmocardiographic analysis - Shchedrina Yu.A. ,; Melnikov D.S. ,; Chernozipunnikova E.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the functional state of boxers using complex indicators calculated on the basis of HRV, with an assessment of the feasibility of their use for qualified athletes. Methods and structure of the study. Qualified boxers aged 21-26 years (n=14) participated in the experiment a week before the competition, with a sports experience of 9 years. We used the «Varicard 2.52» complex for processing cardiointervalograms and analyzing heart rate variability. Results and conclusions. According to the value of the tension index, two boxers revealed a predominance of centralization of heart rhythm control, psycho-emotional tension and a high degree of stress, while others showed optimal tension in regulatory systems. Based on the value of the indicator of activity of regulatory systems, one athlete’s functional state was determined to be optimal, three boxers – a state of moderate tension of functional regulatory systems, two – a state of pronounced tension, and the rest – overstrain of regulatory systems. Assessment of the condition based on the location of the degree of tension of regulatory systems and functional reserves in the phase plane indicated that one boxer has a high probability of developing a premorbid state, while five athletes have a probability of transition to a pre-nosological state. Complex indicators calculated on the basis of HRV analysis data are sensitive in assessing the current state of an athlete, in dynamic control and allow predicting the development of pathological abnormalities even before the appearance of the first symptoms of the disease.